2020
DOI: 10.1038/s41598-020-73695-9
|View full text |Cite
|
Sign up to set email alerts
|

Immune characterization of pre-clinical murine models of neuroblastoma

Abstract: Immunotherapy offers a potentially less toxic, more tumor-specific treatment for neuroblastoma than conventional cytotoxic therapies. Accurate and reproducible immune competent preclinical models are key to understanding mechanisms of action, interactions with other therapies and mechanisms of resistance to immunotherapy. Here we characterized the tumor and splenic microenvironment of two syngeneic subcutaneous (NXS2 and 9464D), and a spontaneous transgenic (TH-MYCN) murine model of neuroblastoma, comparing hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…Mouse neuroblastoma 9464D cells were cultured as previously described. 20 Antibodies Parental anti-mouse PD-1 (EW1-9) rIgG1 was raised using conventional hybridoma technology. 28 Mouse and human anti-PD-1 EW1-9 mIgG1, mIgG2a, mIgG1-N297A, hIgG4 and hIgG4-FALA 26 were constructed as previously described.…”
Section: Animals and Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse neuroblastoma 9464D cells were cultured as previously described. 20 Antibodies Parental anti-mouse PD-1 (EW1-9) rIgG1 was raised using conventional hybridoma technology. 28 Mouse and human anti-PD-1 EW1-9 mIgG1, mIgG2a, mIgG1-N297A, hIgG4 and hIgG4-FALA 26 were constructed as previously described.…”
Section: Animals and Cellsmentioning
confidence: 99%
“…To this end, we compared the immunogenic MC38 model, which bears a high tumor mutational burden (TMB), 19 with the 9464D pediatric neuroblastoma model. 20 21 Pediatric cancers represent a paradigm of immunologically cold tumors with a low mutational load, limited T-cell infiltration, and generally poor responsiveness to anti-PD-1/PD-L1. 22 However, like many adult cancers, there is evidence of PD-1/PD-L1 expression in pediatric tumors, 23 24 supporting the use of preclinical models to better understand how to target PD-1.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results using TH-MYCN +/mice were recently shown, along with a synergistic effect of adding chemotherapy to GD2-directed antibody, analogous to the findings in children with relapsed neuroblastoma in the COG ANBL1221 chemoimmunotherapy trial. [8,17] Moreover, we found a reduced proportion of neuroblasts from 14G2a-treated mice expressed GD2 with decreased MFI when compared with PBS-treated tumors at both the midpoint and terminal time points, suggesting a selective pressure was exerted by 14G2a treatment. Recent work has suggested that GD2 serves as a macrophage checkpoint or "don't eat me" signal between neuroblasts and TAM.…”
Section: Discussionmentioning
confidence: 73%
“…[45] The TH-MYCN mouse model offers many advantages for the study of immune:tumor interactions, acknowledging there are certain limitations including the low frequency of macrometastases. [13,16,17,46,47] Anti-GD2 therapies against neuroblastoma have been studied…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation